Switching Expression or Emotion: Emotional Labor Strategy on Negative Word of Mouth Mediated by Customer Satisfaction - Bakar, Resekiani Mas; Amaliah, Riska; Hidayati, Nurul (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
This experimental study aimed to examine the effect of emotional labor strategy towards the negative WOM mediated by customer satisfaction. Research of emotional labor context has widely examined its impacts on service employees. The limitations in several studies proved that the opportunity in the indirect effect of emotional labor strategy on negative word of mouth (WOM) is still available. Sixty-two participants were involved in this study and divided into two groups (deep acting versus surface acting) by using videos. PROCESS model moderation proved that emotional labor strategy indirectly affects the negative WOM, mediated by customer satisfaction. This study showed that deep acting strategy can enhance customer satisfaction, therefore the negative WOM can be diminished. In contrast, surface acting strategy affects the decrease of customer satisfaction and thus it can raise the intention of the negative WOM. Emotion modification would be more effective through the deep acting strategy in transmitting the positive emotion for the customer, than modification the expression. The satisfaction felt by the customer will decrease the intention to spread negative information about the service provider to other customers.